The Existence of Majaz Mursal in Surah Al-Baqarah from the Perspective of ‘Ilmu Al-Bayan - Lailatul Mauludiyah; Muhamad Amin; Murdiono Murdiono; Renat Sarimov (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2022)
This study analyzed Majaz mursal contained in Surah Al-Baqarah according to Bayan Science Perspective. Majaz mursal is part of majaz lughawi which discusses the use of lafazd not for its original meaning because there is alaqah which is in addition to likeness and there is also currynah that blocks understanding with the meaning of haqiqi (original). Research methods are libraryresearch, and data analysis techniques that use qualitative descriptive analysis techniques. The result of this study is that